2018
DOI: 10.1093/eurpub/cky054
|View full text |Cite
|
Sign up to set email alerts
|

Daily internet time: towards an evidence-based recommendation?

Abstract: This study demonstrates the absence of justification for setting a limit to only 2 h of screen time per day. Significant effects on health seem to appear only beyond 4 h per day and there may be benefits for those who spend less than an hour and a half on internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
4
14
1
3
Order By: Relevance
“…Young survivors in our study prefered recreational sports including soccer for males, and gymnastics, swimming, and dancing for females, and these preferences are similar to those of other school children 27 . A study of screen time in healthy adolescent school children in Switzerland found higher median screen times of 122 minutes per day (compared to 82 minutes per day in our population), though screen time was assessed differently and focused on internet use 28 .…”
Section: Discussioncontrasting
confidence: 57%
“…Young survivors in our study prefered recreational sports including soccer for males, and gymnastics, swimming, and dancing for females, and these preferences are similar to those of other school children 27 . A study of screen time in healthy adolescent school children in Switzerland found higher median screen times of 122 minutes per day (compared to 82 minutes per day in our population), though screen time was assessed differently and focused on internet use 28 .…”
Section: Discussioncontrasting
confidence: 57%
“…For example, online activities may be explored in order to screen for Internet or online game addiction [26]. However, this is an area where clear definitions of risk levels are still lacking [27].…”
Section: General Information (Table 1)mentioning
confidence: 99%
“…Exploring the influencing factors of adolescents’ Internet use behaviors is crucial for the development of targeted interventions. Previous studies have found that age [ 4 , 11 , 12 ], gender [ 4 , 11 , 13 ], academic pressure [ 4 , 14 , 15 ], and parental restrictions [ 6 , 16 ] are related to adolescents’ Internet use behaviors. However, social-cognitive factors of adolescents were not studied well, such as self-efficacy, outcome expectancy, and intention, et al; so far, most studies paid more attention to sociodemographic characteristics and social factors about family and peers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%